Fatty acid, tocopherol, mineral composition, total phenolic, flavonoid and thymoquinone content, and antioxidant potential of Nigella stellaris - Silahtaroglu, Sibel; Güngör, Serife Selma Uras; Ilçim, Ahmet; Kökdil, Gamze (European Journal of Chemistry, 2014)
In the present study, the fatty acid composition of the fixed oil from seeds of Nigella stellaris has been investigated by GC-MS. Linoleic and oleic acids were the major fatty acids. The tocopherols determined by HPLC and α- and δ-tocopherols were detected in the oil. The seeds also were analyzed by ICP-MS to determine mineral content. Ca, P, and K were main elements among seventeen minerals in the seeds. Total phenolic and flavonoid contents of the aqueous methanolic extracts of different plant parts were assessed by Folin-Ciocalteu method and the AlCl3 assay. The seed extract was also analyzed by RP-HPLC analysis for its thymoquinone content. The present study showed that the seed extract contained low amount of thymoquinone. The seed extract exhibited the significantly higher total phenolic and flavonoid content than the extract of aerial part. DPPH radical scavenging activity was used to evaluate the antioxidant capacity of the extracts. Both of the extracts showed high antioxidant activity.